An organified mixture of illite-kaolinite for the removal of Congo red from wastewater. Issue 6 (2nd November 2018) - Omer, Omer Sakin; Hussein, Belal H.M.; Ouf, Abdelfattah Mohamed; Hussein, Mohammed Ali; Mgaidi, Arbi
ABSTRACT: Congo red (CR), an anionic dye, is very harmful to the environment and should be removed via an easy and inexpensive technique. The adsorption of CR from an aqueous solution onto a mixture of illite-kaolinite clay minerals and surfactant-modified illite-kaolinite was investigated at different temperatures. The characterization of the raw clay mixture and the organified sample was confirmed with X-ray diffraction, FTIR spectroscopy, nitrogen gas adsorption at 77 K and transmission electronic microscopy techniques. Factors influencing the adsorption such as pH, adsorbent dosage and temperature were tested. The thermodynamic parameters ΔG°, ΔH° and ΔS° have been calculated, and it was found that the adsorption is exothermic in nature. The isotherm data were fitted by the linear form of the Langmuir and Freundlich models and showed a good fit with the Langmuir approach. The maximum adsorption capacity of surfactant-modified clay (83 mg/g) was found to be around 14 times higher than that of unmodified clay. Kinetic studies of CR on illite-kaolinite and organified illite-kaolinite were evaluated by pseudo-first-order and pseudo-second-order models.